Photo – Histometry A Modified Computer Assisted Morphometric Measurement Program - AL- Kateeb, Huda M; AL-Madfai, Zaid A (Journal of the Faculty of Medicine Baghdad, 2007)
A promotion to a previous computer programmed technique "Photo-Micro Estimation Program" was carried out to compute the exact dimensions of cell and cell fraction in photographs of histological sections. "Visual Basic 6" was used as a language for building of the antecedent application forms. With the aid of a slide micrometer, pixels were substituted for micrometer (μm). The new procedure was termed "Photo-histometry program". To test the suitability of this program, eight photographs of histological sections were selected randomly to be tested. Results were contrasted with those calculated by using ocular lens (calibrated by a slide micrometer). Estimation of RBC diameter (well known, =7-8 μm) was the second step in assessing the adequateness of this new program. Results revealed that this program was simple, fast, adequate and accurate. It was better than the calibrated ocular lens in being more precise (it enumerates up to the fractions of a micrometer)